Penerapan Permainan Kecil Hitam Hijau Untuk Meningkatkan Kemampuan Motorik Kasar Anak Kelas II A SDN Airlangga 1 - Muhammad Dahlan Asyari; Dony Andrijanto; Luthfi Aidin (Pusat Riset dan Inovasi Nasional, 2024)
Education is a conscious and planned effort that aims to develop students' potential to achieve a better life. In the context of physical education, quality learning plays an important role in increasing students' interest and creativity. Physical activity, as taught in PJOK subjects, is very important for the physical-motor development of students, especially in elementary school children. However, observations show that the gross motor development of grade 2 students is not optimal and teachers lack innovation in the use of media and games. Traditional games, such as black and green, can be a solution to improve students' gross motor skills while creating a fun learning atmosphere. This study aims to explore the application of black and green games in improving the gross motor skills of 8-year-old students, with the hope of making a positive contribution to PJOK learning.